Environmental Engineering and Ecological Baseline Investigations along the Yukon River-Prudhoe Bay Haul Road. - Brown,Jerry; Berg,Richard L (1980)
During the period 1975-1978 the Federal Highway Administration sponsored a series of environmental engineering investigations along the Yukon River to Prudhoe Bay Haul Road. In 1976 the Department of Energy joined these investigations with a series of ecological projects which continue to the present. Both agencies' research efforts were conducted on a cooperative basis with CRREL's in-house research program. The objectives of the research focused on (1) an evaluation of the performance of the road(2) an assessment of changes in the environment associated with the road, (3) documentation of flora and vegetation along the 577-km-long transect, (4) methodologies for revegetation and restoration, and (5) an assessment of biological parameters as indicators of environmental integrity. In support of these objectives, specific studies were undertaken that investigated the climate along the road, thaw and subsidence beneath and adjacent to the road, drainage and side slope performance, distribution and properties of road dust, vegetation distribution, vegetation disturbance and recovery, occurrence of weeds and weedy species, erosion and its control, revegetation and restoration, and construction of the fuel gas line. This report presents background information on the region, detailed results of the road thaw subsidence and dust investigations, and summaries of revegation, fuel gas line, vegetation distribution, soil, and weed studies. (Author)